A Novel Shiga Toxin 1a-Converting Bacteriophage of Shigella sonnei With Close Relationship to Shiga Toxin 2-Converting Pages of Escherichia coli. (19th April 2016) - Carter, Christoph C.; Fierer, Joshua; Chiu, Wei Wei; Looney, David J.; Strain, Matthew; Mehta, Sanjay R.
Abstract: In recent studies, strains of non- dysenteriae 1 Shigella (NDS) expressing Shiga toxin have been reported. In this study, we report a novel stx1a -converting bacteriophage of Shigella sonnei associated with travel to Mexico. Phylogenetic comparison between this and other stx- converting phages suggests that toxigenic NDS strains have arisen through separate horizontal transfer events from toxigenic Escherichia coli .